An Intervention Program To Prevent Hypertension Among The Elderly - Taulo Simangusong, Mareta; Novelia, Shinta; Ria Resti, Bs. Warda; Septi Rahayu, Delli; Salsabila, Delsa; Puspita Lestari, Ikeu; Hermawati, Lenny; Ariyanto, Annisa; Naska, Nur Amalia (International Journal of Community Services, 2024)
Hypertension or high blood pressure is a condition when blood pressure is above the normal limit (130/80 mmHg or more). This condition can cause various health complications that are life-threatening if left untreated. In fact, this disorder can cause an increased risk of heart disease, stroke and even death. The aim of community service is to apply scientific theories in the health sector to overcome problems that occur in the field so that they can benefit society, actively participate in the development process health, increasing community empowerment in the health sector, increasing the community's ability academically to apply scientific theories both independently and in groups, helping to overcome problems faced by the government and society using practical scientific methods. Following up on problems found in Meruyung Village/subdistrict, Limo District, Depok Regency, West Java. where elderly people are found to suffer from hypertension, it is necessary to provide health education about hypertension, the impact and prevention of hypertension by evaluating blood pressure examinations and providing herbal medicine with cucumber juice. Out of the 18 elderly people who took part in this activity, 97% (15 people) of the elderly had hypertension. The enthusiasm of the community supports this activity. The strategy for lowering blood pressure is to utilize the abundant natural resources in the area, this time by making cucumber juice to lower blood pressure.